A framework for design of automated lecture timetabling using memetic algorithm / Zarina Zainul Rashid, Roslan Sadjirin and Norhafizah Hashim - Rashid, Zarina Zainul; Sadjirin, Roslan; Hashim, Norhafizah (2009)
Lecture timetabling is a complex real-world problem with many interdependencies. This study describes the framework design of an automated lecture timetabling in educational institutions using soft computing techniques. In this paper, the writerspresent the use of memetic algorithm in the framework design with affective explorative ability to model huge search space. The writers analyse the process, problem and the constraints in timetabling development and study the disciplines that relate to memetic algorithm approach. These requirement specifications are used to design the data structure and the algorithms to produce system architecture for a framework of the automated timetabling system.